Confidentiality of Information when Using QR-Coding - Deineko, Zh.; Sotnik, S.; Lyashenko, V. (IJAISR, 2022)
This work is overview in field of QR codes and their application. The main attention is paid to confidentiality of personal data both when using QR codes and when creating them. The key rules for coding are given. The paper contains main recommendations in order to prevent involuntary transfer of their personal data. Also identified are key aspects that you need to pay attention to in order to make sure that QR-code is secure.
Keywords: information coding; security